Mohd Kamal Hassan: the pearl of the Malay world - Ali, Mohd Mumtaz; Abdul Razak, Mohd Abbas (Dewan Bahasa dan Pustaka, 2025)
The existing literature on the philosophy of education does not reflect the need to meet the requirements of a true and authentic philosophy of education. There is a continuous cry for the resolution of the crisis in higher education. The literature produced by the Muslim thinkers and intellectuals within the last hundred years had not been able to attract the attention of the world. Most Muslim intellectuals and scholars do not remember what had been written by some of the selected Muslim scholars in the recent past on the need for an alternative paradigm of knowledge and education. Hence, it is realized that we must contribute and attract both the intellectuals and scholars, especially the university professors and lecturers to acquaint themselves with new literature by thinkers who have made genuine efforts to resolve the crisis in knowledge and education and promote an integrated model of a holistic educational system. Mohd Kamal Hassan from Malaysia has contributed greatly for this purpose. He not only elaborated on the integrated and holistic education but practically spent all his energy to establish a model of education. In this book we present his ideas on knowledge and education which are not only on theory but recommended practical steps for implementation. The aim and nature of curriculum and education are presented here in this book after going through a long experience of theory and practice. Both the authors of this book have worked with Mohd Kamal Hassan and were part of this contemporary educational exercise. One of the authors, Muhammad Mumtaz Ali, has been fortunate enough to work directly and indirectly with Mohd Kamal Hassan since 1987 until his demise. Most of his views expressed in this book were shared by the authors. The people of the world are looking for modernization and development of their countries. Here is a practical model of education which was conceptualized and put in practice by Mohd Kamal Hassan which, if implemented on a large scale can guarantee the development that is free from corruption and crime. The theory and practice have been provided by Mohd Kamal Hassan. We now need to transmit this to the new generations so that they can understand it and bring it to greater heights with new creations and efforts. Now it is up to the readers to benefit from it. Muhammad Mumtaz Ali Mohd Abbas Abdul Razak